Using Twitter for Student Learning in Now Era - Pinasthika Septiani; Deli Nirmala (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2020)
Twitter is a site that offers a social network of  microblogs thus allows users to receive and send messages called tweets. The purpose of this study to examine how social media can influence students in building ideas and motivation for their own learning and to analyse how Twitter affects on knowledge purpose. In this research, the writer uses contructivism theories to know purpose of learning by using Twitter and sample research method to find out how students use Twitter in every aspect of their learning and how effectively this online application for study. After observing this study, the writer can represent using twitter as a media for learning can build the creativity and self-reliance students, also can build their own knowledge.Keywords: contructivism, learning, social media, twitter